Evaluating the impact of operating a falls prevention community of practice on falls in a residential aged care setting - Francis-Coad, J.; Haines, T.; Etherton-Beer, C.; Nobre, D.; Hill, Anne-Marie (2018)
© 2018 Asia Pacific League of Clinical Gerontology & Geriatrics. Background/Purpose: Falls are a leading adverse event in residential aged care (RAC) settings with prevention a global aim. The purpose of this study was to determine whether operating a falls prevention community of practice (CoP) delivering evidence-based prevention interventions could change the rate of falls and injurious falls in a RAC setting. Methods: A prospective quasi-experimental pre/post design was conducted. Participants were 13 RAC sites (779 beds) of a single RAC organization, with 20 multidisciplinary staff volunteering as CoP members. Results: Falls rates pre CoP were 10.1/1,000 occupied bed days (OBD) compared with 10.9 /1,000 OBD post CoP operation [coefficient 0.7, 95% CI -33.5, 34.9 (p=0.967)]. This was confounded by identified differences and changes in defining falls between sites. The rate of injurious falls resulting in fractures pre CoP was 0.2/1,000 OBD compared with 0.1/1,000 OBD post CoP; [coefficient -0.3, 95% CI -1.1, 0.4 (p=0.423)] . Conclusion: A falls prevention CoP operating for 18 months was unable to reduce falls rates in that time frame but there was a trend to a reduction in falls resulting in fracture. Additional time for implementation and evaluation of falls prevention interventions will be required in complex settings, such as RAC organizations, in the absence of additional funding. Valid comparisons of falls rates and injurious falls rates within the RAC population require the adoption of standardized definitions to improve reporting reliability.